Relationship between the risk of suffering from diabetes mellitus and anthropometric indexes in a rural town of Tucumán, Argentina - Du Plessis, María Cristina (2018)
Introduction. The assessment of abdominal fat with the ratio waist size (RCT) and waist hip ratio (RCC) are simple measurements to obtain in primary care and evaluate the potential cardiovascular and metabolic risk. The aim of the present study was to determine the relationship between the risk of suffering from diabetes mellitus 2 (DM2) and anthropometric indexes in a rural population of Tucumán,  rgentina. Methods. Observational, analytical and transversal study was carried out. A total of 113 people aged 18 to 64 years were selected by systematic random sampling. The Finnish Diabetes Risk Score test was used to determine the risk of having DM2. The anthropometry evaluated was: body mass index (BMI), RCT, RCC. Fisher’s test, Chi square, Pearson (r) were applied and ROC curves were analyzed. α = 0.10 was considered. Results. 18% (20) had a high risk of developing DM2 in the next 10 years. There was a significant positive correlation between RCT and risk of DM2 (r = 0,65) as well as RCC and risk of DM2 (r = 0,36). A higher risk of DM2 was found in people with overweight and obesity. The cut-off point of 0,6 on the ROC curve showed a sensitivity of 80% and a specificity of 61% to discriminate patients with RCT who had a high risk of developing DM2 (p<0,001). Conclusions. In the  sample studied (n = 113), 18% (20) had a high risk of developing DM2, there was a positive correlation between RCT, RCC and risk of developing DM2. The RCT had high sensitivity and specificity to discriminate the risk of presenting DM2